Youth Religiosity in Chile: a Territory Yet to Be Explored - Cerda-Planas, Catalina (International journal of Latin American religions, 2021)
Although youth religiosity is a strongly developed research topic in places like the USA or Europe, in Chile, there is an important lack of knowledge in this regard, primarily due to the absence of a specialized and systematic study of it. However, some available data allows identifying how much we actually know and what is yet to be researched. In the following article, descriptive findings of the last 20 years of research on youth religious affiliation, beliefs, and practices are reported. Finally, synthesis and discussion of the knowledge achieved to date are proposed, and the selected route for further research on the topic is presented based on the results.